Effect Of Cadmium Element On The Ecological Status Of Irrigated Soils In Nishan District - Nizamov Sobirjon A'laevich.; Riskieva Khurshida Tursunovna.; Baxodirov Zafar Abduvalievich.; Kuziev Jakhongir Madaminovich.; Mirsodiqov Miraziz Mirvoxidovich. (Zien Journals, 2022)
The article presents data on the accumulation, excess of the maximum permissible concentration of cadmium in irrigated sierozem-meadow, desert-sandy, as well as gray-brownmeadow soils of the Nishan district of the Kashkadarya region
Keywords: Irrigated serozem-meadow; desert-sandy; gray-brown-meadow soils